Aspek mikrobiologis susu sapi murni dengan penambahan sari rimpang Bangle (Zingiber cassumunar Roxb) - Masnur Turnip, Rosalia Juniati Nahak, Siti Khotimah, (Universitas Tanjungpura, 2014)
Milk is food which contains nutrients such as proteins, fats, carbohydrates, minerals, and vitamins. Milk is also a growing medium for microorganisms. This study aims to determine the quality of pure cow's milk after bangle rhizome extract (Zingiber cassumunar Roxb) being added to it. The study was conducted from January to March 2014. The parameters observed in this study is TPC (Total Plate Count) by using the pour plate method, the calculation of the amount of coliform by using MPN method, the computation of time reduction by using reductase method and organoleptic test by using taste panel method. Based on the research findings, it was revealed that the extract of rhizome bangle added to the milk at a concentration of 2,4% can reduce the total number of bacteria from 2,47 Ã— 105 to 0,73 Ã— 105, reduce the amount of coliform bacteria from 210 CFU / ml to 7 CFU / ml and prolong the time reduction up to 700 minutes (11.6 hours) and make the results of organoleptic test accepted by the panelists.